62 Safe critically ill patient transfer- a simulation pilot for nurses (script). (17th November 2016) - Needler, V; Sutton, P; Burnett, G; Pettit, J; Wong, A; Lee, G; Butterill, T; Gay, C; Riby, S; Graby, M
Abstract : The ability to safely transfer critically ill patients between departments or hospitals is an essential skill required to meet care needs; few health care professionals have the opportunity to practice these skills before taking part in real life transfers. We designed an interactive learning day for nurses using evidenced based workshops and simulation scenarios to capture the essence of transferring patients. Using a high fidelity simulation mannequin, mobile filming equipment and training ambulance nurses were fully immersed in the patient journey. Half of the group were positioned remotely observing a live feed and were able to provide peer to peer feedback, a second scenario allowed the nurses to swap from participator to observer. We measured an increase in confidence levels in all 13 participants using pre and post course questionnaires to explore key areas of learning for future courses.